Prevalence Of Hypertension and Its Risk Factors Among Class III and Class IV Government Employees in Ahmedabad - Dhara Prajapati; Geeta Kedia (Medsci Publications, 2015)
Background: The developing country including India is experiencing epidemiological transition from communicable to Non communica- ble diseases and hypertension has emerged as a significant public health problem in both urban and rural areas. The present study was conducted to assess prevalence of Hypertension and its risk-factors in government employees of Ahmedabad city. Methodology: It was a cross-sectional study conducted among 600 government employees of B.J. Medical College of Ahmedabad, Guja- rat. Data was collected using a pre-tested, questionnaire and Blood pressure was measured. Results: Prevalence of hypertension was 17 % in males and 19.67% in females. Prevalence of hypertension was 53.28 % in age group of 55 years and above. 10.66 % males and 11.66 % females were found hypertensive on examination. Based on Odds Ratio, History of To- bacco consumption, family history of hypertension, low vegetables and fruits intake and higher waist circumference was associated with more risk of hypertension. Conclusions: History of Tobacco consumption, family history of hypertension, low vegetables and fruits intake and higher waist cir- cumference increase the risk of hypertension.